Impact of Additional Chromosomal Aberrations on the Disease Progression of Chronic Myelogenous Leukemia - Krishna Chandran, Ramachandran; Geetha, Narayanan; Sakthivel, Kunnathur Murugesan; Suresh Kumar, Raveendran; Jagathnath Krishna, Kumarapillai Mohanan Nair; Sreedharan, Hariharan (Frontiers in Oncology, 2019)
The emergence of additional chromosomal abnormalities (ACAs) in Philadelphia chromosome/BCR-ABL1 positive chronic myeloid leukemia (CML) is considered to be a feature of disease evolution. However, their frequency of incidence, impact on prognosis and treatment response effect in CML is not conclusive. In the present study, we performed chromosome analysis of 489 patients in different clinical stages of CML by conventional GTG-banding, Fluorescent In Situ Hybridization and Spectral Karyotyping. Among the de novo CP cases, ACAs were observed in 30 patients (10.20%) with lowest incidence, followed by IM resistant CP (16.66%) whereas in AP and BC, the occurrence of ACAs were higher and it were about 40.63% and 50.98% respectively. The frequency of occurrence of ACAs were compared between the study groups and found that the incidence of ACAs were higher in BC compared to de novo and IM resistant CP cases. Likewise, it was higher in AP patients when compared between de novo and IM resistant CP cases, mirroring the fact that cytogenetic evolution with disease progression in CML. In addition, we observed 10 novel and 10 rare chromosomal aberrations among the study subjects. This study pinpoints the fact that the genome of the advanced phase patients were highly unstable and this environment of genomic instability is responsible for the high occurrence of ACAs. Treatment response analysis revealed that compared to initial phases, ACAs were associated with adverse prognostic effect during the progressive stages of CML. This study further portrayed the cytogenetic mechanism of disease evolution in CML.